2020
DOI: 10.20944/preprints202007.0399.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

miR-142-3p Reduces the Size, Migration and Contractility of Endometrial and Endometriotic Stromal Cells by Targeting Integrin- and Rho GTPase-related Pathways that Regulate Cytoskeletal Function

Abstract: Downregulated microRNA-142-3p signaling contributes to the pathogenesis of endometriosis [1] [2], an invasive disease where the lining of the uterus grows at ectopic locations, by yet incompletely understood mechanisms. Using bioinformatics and in vitro assays, this study identifies cytoskeletal regulation and integrin signaling as two relevant categories of miR-142-3p targets. qPCR revealed that miR-142-3p upregulation in St-T1b cells downregulates ROCK2, CFL2, RAC1, WASL and ITGAV. qPCR and Western-blotting … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
1
1
0
Order By: Relevance
“…2A). Because ITGB3 and ITGAv are well known to be regulated by miR-150 and miR-142, respectively [18][19][20], we confirmed that miR-150 and miR-142 were downregulated in our two AUY922 resistant NSCLC cell lines (Fig. 2B).…”
Section: Integrin αVβ3 (Itgav 3) Induces Ayu922 Resistance Via Fak Activationsupporting
confidence: 72%
See 1 more Smart Citation
“…2A). Because ITGB3 and ITGAv are well known to be regulated by miR-150 and miR-142, respectively [18][19][20], we confirmed that miR-150 and miR-142 were downregulated in our two AUY922 resistant NSCLC cell lines (Fig. 2B).…”
Section: Integrin αVβ3 (Itgav 3) Induces Ayu922 Resistance Via Fak Activationsupporting
confidence: 72%
“…Previous studies have reported that TSPAN7 [ 24 ] and ITGB3 [ 20 ] are induced by microRNA-150 (miR 150) downregulation activity and that ITGAv is targeted of miR-142 [ 18 , 19 , 25 ]. Since both TSPAN7 and ITGB3 are co-direct targets of miR-150 [ 20 , 24 ], we examined whether this regulatory molecule controlled EMT and FAK activity through the blockade of TSPAN7 and ITGB3 expression, respectively.…”
Section: Resultsmentioning
confidence: 99%